Haemato-biochemical Profile of Haemoprotozoan Infected Cows, Buffaloes, and Horses - Odedara, Arjun B.; Thakre, Bhupendra J.; Padodara, Ramesh J.; Kalaria, Vinay A.; Singh, Vivek K.; Vasava, Amrita A.; Sharma, Arun K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was conducted to evaluate haematological and biochemical alterations in haemoprotozoan infected animals  (n = 60; cows 20, buffaloes 20 and horses 20) compared to healthy ones (n= 20, 20 & 20, respectively) in and around Junagadh region  in Gujarat. There was a significant (p
Keywords: Biochemistry; Haemoprotozoan; Haematology; Horses; Oxidative stress; Ruminants